Optimization of ultrasound-assisted extraction of phenolic antioxidants from Lotus corniculatus - Fumić, Barbara (Array, 2019)
Ultrasound-assisted extraction of phenolic antioxidants from Lotus corniculatus was optimized using response surface methodology. The extraction was performed according to the Box–Behnken design with ethanol concentration, temperature, and pH, as independent variables. The responses were extraction yield, DPPH radical scavenging activity (RSA) IC50 and content of different phenolic compounds (total phenols, flavonoids and phenolic acids, as well as quercetin, kaempferol and genistein derivatives). The models were used to calculate best conditions for maximal extraction of phenolic compounds and antiradical activity. Use of the optimized extraction parameters increased the content of quercetin and kaempferol derivatives more than tenfold (from 6.07 to 65.10 mg mL–1 and 6.69 to 92.75 mg mL–1, respectively). The results of this work stress the importance of careful selection of conditions for flavonoids extraction. Abundance of bioactive phenolics in L. corniculatus extracts obtained under optimized extraction conditions opens the possibility for wider utilization of this plant.